Na+, K+-ATPase response to neurotensin is altered by streptozotocin administration - Ordieres López, María Graciela (2013)
Neurotensin is a basic tridecapeptide which can act as a neuromodulator or a neurotransmitter and binds to a group of receptors. Neurotensin is able to inhibit Na+, K+-ATPase activity, an effect blocked by the presence of antagonist SR48692, suggesting the involvement of high affinity neurotensin (NTS1) receptor. Diverse evidences suggest a relationship between neurotensinergic system and glycemia levels. For this reason, potential Na+, K+-ATPase regulation by neurotensin in brain membranes obtained from rats turned hyperglycaemic was explored. As a model to produce diabetes mellitus, rats were administered with Streptozotocin (STZ), a specific toxic agent to the pancreatic beta cells. Our findings indicated that Na+, K+-ATPase activity in synaptosomal membranes isolated from diabetic rats failed to respond to neurotensin. The treatment decreased the affinity of NTS1 receptor for neurotensin and the expression of Na+, K+-ATPase alpha3 subunit in cerebral cortex. The results led us to conclude that STZ administration alters the response of Na+, K+-ATPase to neurotensin. Such effect seems to involve a decrease in enzyme alpha3 isoform expression and NTS1 receptor affinity for neurotensin.